FRI0110 Methotrexate monotherapy in real life: a drug survival analysis. comparison between very early arthritis and early arthritis cohorts. (15th June 2017) - Anelli, MG; Rotondo, C; Righetti, G; Rinaldi, A; Perniola, S; Nivuori, M; Lopriore, S; Lopalco, G; Laselva, G; Scioscia, C; Cacciapaglia, F; Lapadula, G; et al.
Abstract : Background: Methotrexate (MTX) is the first line drug suggested in the ACR/EULAR guidelines to treat the rheumatoid arthritis (RA) (1) and spondylarthritis (SpA). Although MTX efficacy is demonstrated by high levels of evidences, maximum benefit might require interventions even earlier. For this reason, it is suggested to identify the patients (pts) with symptom onset of less than 12 weeks, that is very early arthritis, to obtain better outcomes. Few data are available by the clinical practice on MTX monotherapy (MTXm) survival in very early or early arthritis pts. Objectives: We aim to evaluate the presence of different outcomes in MTXm drug survival and MTX efficacy between Very Early arthritis (VEA) pts (less than 12 weeks from symptom onset) and Early arthritis (EA) pts (12–52 weeks from symptom onset), and between early RA pts and early SpA pts. Methods: On 305 pts, we selected 219 pts (30 pts diagnosed as VEA (4, 2 (4) weeks from symptom onset) and 155 pts as EA (25, 7 (25) wks from symptom onset) in which MTXm could be started. The RA pts were 93 and SpA pts were 126. To assess the MTXm persistency the Kaplan-Meier survival curves analysis was performed and Cox regression analysis was used to assess clinical predictors of MTXm suspension. The results are expressed as mean±standard deviation or median (interquartile range). A p≤0.05 was set for statistically significant. Results: No difference in MTXm survival was found between VEA pts 95, 5 (36) wks and EA 92, 5 (10) wks (p=0, 38) (Fig.1 a). We observed a significant difference in drug survival between early RA pts 63 (16) wks) and early SpA pts 112, 7 (15, 8) wks (p=0, 001) (Fig.1 b). In 55% early RA pts and in 45% early SpA pts the biotechnology drug needs to be added because of disease flare. In the remaining pts a low disease activity (DAS≤3, 2) was observed. No adverse events were recorded in follow-up period. In early RA pts predictors of shorter MTXm survival were younger age at diagnosis (p=0, 004), lower dose of MTX (p=0, 032), earlier diagnosis from symptom onset (p=0, 0001), higher titer of rheumatoid factor (p=0, 037) and female gender (p=0, 019). In early SpA pts the only predictor of shorter MTXm survival was younger age at diagnosis (p=0, 0, 37). Smoking, disease activity at diagnosis and BMI were not predictors of MTXm survival. Conclusions: The MTXm survival is not influenced by VEA or EA diagnosis. The RA seems to be less responder to MTXm than SpA. It might be due to the difficult to capture the earliest phase of disease, as circulating antibodies might appear years before the onset of symptoms in RA, and biomarkers reflecting bone destruction are elevated before arthritis is present, as described in previous studies. In particular, might be pay attention to younger pts, female gender and pts with higher titer of rheumatoid factor as they seem to present a more resistant RA disease. A high dose of MTX and earlier interventions are suggested in RA to improve the clinical outcome of patients and the MTXm survival. References: Smolen JS et. Al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis 2014;73:492–509. Disclosure of Interest: None declared